A Prática Desportiva e o Bem-estar Subjetivo. Um estudo realizada num ginásio em Vila Nova de Gaia - Ana Carolina Rocha Silva (2017)
Nowadays, the demand for welfare and quality of life has increased, and it is known that regular sports practice is an important factor in disease prevention as well as promoting health and well being. In that direction of thought, we look through this study to analyze the relationship between physical activity performed in a gymnasium and subjective well being. A total of 396 adults with a gymnasium membership in Vila Nova de Gaia, aged between 18 and 72 years old (average age 34.53 ± 11.744 years), of whom 66.9% were female (267) and 33, 1% were male (132) participated in this study as a sample. For the evaluation of Life Satisfaction, a version adapted from the Satisfaction Whith Life Scale (SWLS; Diener, Emmons, Larsen & Griffin, 1995) by Figueiras et al (2010) was used. In order to evaluate the positive and negative effects, a translated and adapted version of the Scale: Positive and Negative Affect Schedule (PANAS, Watson et al., 1988), by Fonseca (2006) was used. From the results obtained, we concluded that the sample had levels of subjective welfare above the average, and did not present statistically significant differences according to gender and age. There were significant results related to positive effects in individuals who practiced physical activity more than four times per week and also significant and positive results in those who also practiced physical activity outside of the gymnasium.